Empirical Testing of Capital Structure and Profitability as Mechanisms to Enhance Firm Value - Emillia Nurdin; F Fitriaman; Warniyatih Nur Aqurat (Universitas Pendidikan Indonesia, 2023)
This study examines the effect of capital structure and profitability on the firm value in Mining Companies that have been listed on the Indonesia Stock Exchange (IDX). The sample selection technique was carried out using the purposive sampling method so that 12 companies were obtained as samples. This research uses quantitative methods and multiple linear regression analysis was utilized to examine the relationship between the variables under consideration. From the research results, it was found that capital structure has a positive effect on firm value, indicating that an increase in capital structure will enhance the value of mining companies listed on the Indonesia Stock Exchange. The research results align with the trade-off theory, which suggests that judicious use of debt financing can increase firm value. The research results also found that profitability has a positive effect on firm value, as higher profitability enhances firm value. The results of this study align with the signaling theory, the level of company profitability can be a positive signal for investors to invest. The implications of this research are aimed at three different groups: investors, companies, and future researchers. The research concludes that increasing capital structure and profitability can enhance firm value. This study provides new insights into the relationship between capital structure, profitability and firm value in the context of mining companies listed on the Indonesian Stock Exchange (IDX).